'A study on factors that affecting the training transfer at Bank Rakyat Branches in Kuala Lumpur' / Nurul Ain Othman - Othman, Nurul Ain (2013)
For the last few decades, the effectiveness of transfer of training had been look up seriously by the organization. This study aims to determine which factors that affect the transfer of training in Bank Rakyat. There are four factors that will be study which are self-efficacy, openness to experience, affective commitment, peer organizational support and training design. The factors were known as independent variables. As for the dependent variables, the researcher chooses transfer of training. In this study, the researcher chooses 140 of employees from selected Bank Rakyat branches in Kuala Lumpur region. The SPSS 16.0 is used to analyzing the data. For testing the reliability of the questions, researcher used the reliability test. Meanwhile for the hypotheses testing, the researcher used correlations analysis and multiple regression analysis. The result indicates that, only 3 variables have a positive and significant relationship with the training transfer.